SURVEY OF GASTROINTESTINAL PARASITES OF THE CENTER FOR SCREENING OF WILD ANIMALS FROM SÃO LUÍS, MARANHÃO STATE, BRAZIL - FIGUEIREDO, M. A. P.; MANRIQUE, W. G.; NOGUEIRA, R. M. S. (Ars Veterinaria, 2018)
The objective was to identify the gastrointestinal parasites of wild animals received by the Center for Screening of Wild Animals from São Luis, Maranhão State, Brazil. The fecal samples were collected from 297 animals, of which 150 (50.5%) were birds, 132 (44.5%) mammals and 15 (5%) reptiles. A total of 262 samples (227 individual and 35 pools) were analyzed by the method of sedimentation and flotation, 102 animals were parasitized by helminthes and/or protozoa, 39 of which belonged to the order Primate, 18 to the Carnivorous order and 12 to the Psittaciformes order. The mammals had the greatest diversity of eggs of gastrointestinal parasites: Strongyloides sp., hookworm type, Spirometra sp., Ascaris sp., Trichuris vulpis, Capillaria sp., Strongyloidea, Ancylostomidae , taenid and oocysts of coccidian. In the samples of birds were diagnosed eggs of the genera Dispharynx, Ascaridia, Echinostoma and oocyst of coccidian. In the reptiles, the number of gastrointestinal parasites was low, being identified oocyst of coccidian in three jiboia (Boa constrictor) and Capillaria sp. in an iguana (Iguana iguana). It was concluded that wild animals act as hosts for various species of parasites and to establish the dynamics and parasitic fauna of these animals at the screening center is an excellent alternative for studies ex situ.